Magnetic Resonance Imaging in the Management of Significantly Displaced Adolescent Posterior Sternoclavicular Joint Injuries. Issue 5 (3rd May 2023) - Tytherleigh-Strong, Graham; Cuthbert, Rory; Poutoglidou, Freideriki; Tang, Quen
Abstract : Background: Computed tomography (CT) scans are the standard imaging modality for the diagnosis and treatment guide for adolescent posterior sternoclavicular joint (SCJ) injuries. However, the medial clavicular physis is not visualized and it is not possible to differentiate between a true SCJ dislocation and a physeal injury (PI). An magnetic resonance imaging (MRI) scan can visualize the bone and the physis. Methods: We treated a series of patients with adolescent posterior SCJ injuries diagnosed on CT scan. Patients underwent an MRI scan to differentiate between a true SCJ dislocation and a PI and to further differentiate between a PI with or without residual medial end clavicular bone contact. Patients with a true SCJ dislocation and a PI with no contact underwent an open reduction and fixation. Patients with a PI with contact were treated nonoperatively with repeat CT scans at 1 and 3 months. At final follow-up SCJ clinical function was assessed using Quick-DASH, Rockwood, modified Constant, and single assessment numeric evaluation (SANE) scores. Results: Thirteen patients (2 female and 11 male) with an average age of 14.9 years (12 to 17) were included in the study. Twelve patients were available at final follow-up (mean 50 mo, 26 to 84). One patient had a true SCJ dislocation and 3 had an off-ended PI and were treated with an open reduction and fixation. Eight patients had a PI with residual bone contact and were treated nonoperatively. For these patients serial CT scans showed that the position was maintained, with a serial increase in callus formation and bone remodeling. The average follow-up was 42.9 months (24 to 62). At final follow-up the mean Quick-disabilities of the arm, shoulder and hand (DASH) was 0.4 (0 to 2.3), Rockwood was 15, modified Constant was 98.8 (89 to 100) and SANE was 99.5% (95 to 100). Conclusion: In this case series of significantly displaced adolescent posterior SCJ injuries MRI scans allowed identification of true SCJ dislocations and off-ended PIs, which were successfully treated by open reduction, and PIs with residual physeal contact which were successfully treated nonoperatively. Level of Evidence: Level IV—case series.